(untitled) (Bioscience Journal, 2022)
This study aimed to verify the efficiency of multilines in reducing blast progress and their potential benefits to phenotypic stability in rice. The experiments were conducted in the 2016/17 and 2017/18 agricultural years. A randomized block design was performed with three replications, evaluating 12 lines and a multiline, which consisted of five lines from the Cultivation and Use Value (CUV) test. The multiline presented an estimated grain yield above the average of experiments of around seven bags ha-1 and superior performance in early flowering, justifying the high phenotypic stability for these characters. In this case, the line selection for composing the multiline was favorable and efficient, highlighted by a higher agronomic performance than most lines of the CUV test. The multiline is an adequate strategy to provide higher phenotypic stability and reduce blast progress in the field.